c.3 IB - Singh, Samar (New Delhi, 2004)
A comprehensive volume on legal provisions for maintaining law and order expecially during communal unnst, this book also provides guide lines to promote communal harmony. All the legal provisions and the executive instructions on The subject have been explained in a cogent manner
Keywords: Public order-Legal aspects